Aromatase inhibitors use and risk for cardiovascular disease in breast cancer patients: A population-based cohort study. (October 2021) - Sund, Maria; Garcia-Argibay, Miguel; Garmo, Hans; Ahlgren, Johan; Wennstig, Anna-Karin; Fredriksson, Irma; Lindman, Henrik; Valachis, Antonis
Abstract: Background: Prior studies regarding use of Aromatase inhibitors (AIs) and risk for cardiovascular disease (CVD) have shown conflicting results. This retrospective cohort study aimed to investigate whether AIs use affects risk for CVD events in postmenopausal breast cancer survivors. Methods: Using a retrospective cohort study design, four CVD outcomes; heart failure or cardiomyopathy, arrhythmia, acute ischemic heart disease and ischemic stroke or Transient Ischemic Attack were compared with uni- and multivariate Cox regression analyses according to exposure to endocrine therapy (use of AI, tamoxifen or AI/tamoxifen sequentially) or no endocrine therapy. Results: In total 15815 postmenopausal women, surgically treated to early breast cancer during 2006–2012, were included. No significantly increased risk for CVD events was observed in patients with AI use in the whole cohort. However, two subgroup analyses showed increased risk for CVD events in the AI/tamoxifen sequential group; heart failure in patients older than 75 years (Hazard Ratio (HR) 2.44; 95% Confidence Interval (CI): 1.32–4.54) and arrhythmia in patients without prior CVD (HR 1.45; 95% CI: 1.01–2.10). An increased risk for arrhythmia and acute ischemic heart disease in patients with at least four years of AI treatment compared with no or short-time exposure was observed (HR 2.12; 95% CI: 1.40–3.25 for arrhythmia; HR 2.03; 95% CI: 1.15–3.58 for ischemic heart disease). Conclusion: Our results indicate an increased risk for ischemic heart disease and arrhythmia in patients treated for more than four years with AIs. This should be considered in the risk-benefit assessment concerning endocrine therapy. Highlights: A potential negative impact of aromatase inhibitors as adjuvant treatment on risk for cardiovascular events has been proposed. We investigated the risk for cardiovascular events in breast cancer patients treated with aromatase inhibitors in a retrospective cohort study. Use of aromatase inhibitors for four years or more was associated with increased risk for ischemic heart disease and arrhythmia. Our findings support the need to include this information to the risk-benefit assessment concerning endocrine therapy.